Health Services Research and Health Economy – Quality Care Training in Gynaecology, with Focus On Gynaecological Oncology - Lux, M. P.; Fasching, P. A.; Loehberg, C. R.; Jud, S. M.; Schrauder, M. G.; Bani, M. R.; Thiel, F. C.; Hack, C. C.; Hildebrandt, T.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2011)
In the era of cost increases and reduced resources in the German healthcare system, the value of health services research and health economics is increasing more and more. Health services research attempts to develop concepts for the most effective ways to organise, manage, finance and deliver high-quality care and evaluates the implementation of these concepts with regard to daily routine conditions. Goals are the assessment of benefits and the economic advantages and disadvantages of new and established diagnostic methods, drugs and vaccines. Regarding these goals, it is clear that health services research goes hand in hand with health economics, which evaluates the benefits of diagnostic and therapeutic procedures in relation to the costs. Both scientific fields have focus principally on gynaecology and particularly on gynaecological oncology in Germany, as can be seen by numerous publications. These present several advantages compared with clinical trials – they uncover gaps in health care, question the material, staffing and consequently the financial resources required and they allow the estimation of value and the comparison of different innovations to identify the best options for our patients.
Keywords: health services research; health economics; gynaecology; education; benefit; financing; QALY